Behavioural responses of migratory shorebirds to disturbance at a high-tide roost - Lilleyman, Amanda; Franklin, Donald C.; Szabo, Judit K.; Lawes, Michael J. (Emu, 2016)
Many long-distance migratory shorebirds are threatened. Anthropogenic disturbance at roost sites on their non-breeding grounds might exacerbate other threats by leading to depletion of fat reserves and forcing birds away from traditional sites. We measured the response (occurrence of alarm flight and resettlement time) of roosting shorebirds knots (Calidris spp.) and sand plovers (Charadrius spp.) to anthropogenic and natural disturbances. Flight was the most common response (0.86 alarm flights h-1). The likelihood of an alarm flight was most strongly influenced by flock size and distance to the disturbance agent, smaller flocks closer to the agent being more likely to take flight. Sand plovers had shorter flight-initiation distances than knots but took longer to resettle after disturbance. Resettling duration was also influenced by time since arrival on the non-breeding grounds, being longest shortly after birds arrived. Energy budget models suggested that 10 alarm flights per day increased daily energy expenditure by 4.5–4.7% for knots and 7.5–7.8% for sand plovers. This may reduce energy reserves to levels below the threshold that can be replenished by normal intake rates and thus negatively affect survival or reproductive success. Increased disturbances may place additional and unsustainable pressures on populations that are already experiencing major declines.